Improving the effectiveness of drug safety alerts to increase adherence to the guideline for gastrointestinal prophylaxis. (January 2017) - Lilih, Soufiane; Pereboom, Marieke; van der Hoeven, Ruud T.M.; Mantel-Teeuwisse, Aukje K.; Becker, Matthijs L.
Highlights: We implemented a clinical decision support system for gastrointestinal prophylaxis. Prescriptions for gastrointestinal prophylaxis increased from 84.0 to 94.5%. The number of drug safety alerts decreased by 78.2%. Abstract: Objective: Gastrointestinal bleedings are the most frequently occurring reason for medication-related hospital admissions, which are potentially preventable. We implemented a clinical decision support system that recommends to prescribe gastrointestinal prophylaxis in patients with an increased risk according to the Dutch guideline. Our primary objective was to determine whether the implementation resulted in improved compliance with this guideline for gastrointestinal prophylaxis. A secondary objective was to determine whether implementation resulted in a reduction of the number of drug safety alerts. Materials and methods: This intervention study was performed at the Spaarne Gasthuis, a teaching hospital, using Epic as hospital information system. We selected prescriptions with an indication for gastrointestinal prophylaxis according to the guideline, in the three months before and after implementation of the clinical decision support in November 2014. We analyzed whether gastrointestinal prophylaxis was prescribed more frequently after implementation using the Pearson's Chi-square test and the change in the number of drug safety alerts. Results: Before implementation in 84.0% of the included 2064 prescriptions gastrointestinal prophylaxis was co-prescribed. After implementation this percentage increased to 94.5% of the 2269 prescriptions (p < 0.001). The number of drug safety alerts decreased by 78.2% from 980 to 217 alerts. Conclusion: The introduction of a clinical decision support system for gastrointestinal prophylaxis improved adherence to the Dutch guideline. This was most likely due to a reduction in the number of irrelevant drug safety alerts.